DNA Damage Response: A Molecular Lynchpin in the Pathobiology of Arteriosclerotic Calcification. Issue 7 (July 2020) - Duer, Melinda; Cobb, Andrew M.; Shanahan, Catherine M.
Abstract : Vascular calcification is a ubiquitous pathology of aging. Oxidative stress, persistent DNA damage, and senescence are major pathways driving both cellular and tissue aging, and emerging evidence suggests that these pathways are activated, and even accelerated, in patients with vascular calcification. The DNA damage response—a complex signaling platform that maintains genomic integrity—is induced by oxidative stress and is intimately involved in regulating cell death and osteogenic differentiation in both bone and the vasculature. Unexpectedly, a posttranslational modification, PAR (poly[ADP-ribose]), which is a byproduct of the DNA damage response, initiates biomineralization by acting to concentrate calcium into spheroidal structures that can nucleate apatitic mineral on the ECM (extracellular matrix). As we start to dissect the molecular mechanisms driving aging-associated vascular calcification, novel treatment strategies to promote healthy aging and delay pathological change are being unmasked. Drugs targeting the DNA damage response and senolytics may provide new avenues to tackle this detrimental and intractable pathology.